Percutaneous Pulmonary Valve Implantation (PPVI) with Melody®: First Ever Case Report in South Asia - Fatema, Nurun Nahar; Hossain, Md Rabiul (Journal of Bangladesh College of Physicians and Surgeons, 2015)
An eleven years old boy was diagnosed as a case of Tetralogy of Fallot (TOF) with absent left pulmonary artery (LPA) since two years of age. He had history of total corrective surgery in 2007 from India. He developed severe right pulmonary artery origin stenosis, severe tricuspid and pulmonary valve regurgitation after surgery and redo surgery was performed in 2009. During redo surgery an orthotropic conduit was placed between right ventricular (RV) out flow tract and pulmonary artery. He developed significant conduit dysfunction in the form of stenosis and regurgitation in 2011 and planned for Melody® trans-catheter pulmonary valve replacement. Finally in 25th December 2012, first ever case of pulmonary valve replacement in South Asia was performed in catheterization laboratory of CMH Dhaka with technical support from a Saudi cardiac team. Patient was discharged three days after the procedure with a fully functioning Melody® valve without any stenosis or regurgitation. J Bangladesh Coll Phys Surg 2014; 32: 102-106